EFFECTS OF LEARNING METHODS AND EMOTIONAL INTELLIGENCE ON THE ABILITY TO WRITE ENGLISH NARRATIVE TEXT - Suwardin Mbulu; Rifari Baron (INFERENCE: Journal of English Language Teaching, 2019)
This study aims to show the influence of Learning Methods and Emotional Intelligence on the Ability to Write Students' English Narrative Texts. The research hypotheses tested include: 1).Effect of Learning Methods on the Ability to Write English Narrative Texts. 2).The Effect of Emotional Intelligence on the Ability to Write English Narrative Texts.3).The interaction effect of Learning Methods and Emotional Intelligence on the Ability to Write English Narrative Texts. This study uses an experimental method. Research results:1).There is a significant influence of learning methods on students' ability to write English narrative texts at students.This is evidenced by the summary of sig values 0.016<0.05,with Fcount=6.062. 2).Theren is a significant influence of emotional intelligence on students' ability to write English narrative texts at students. This is evidenced by the summary value of sig 0,000<0.05,with Fcount=15.638. 3).There is a significant interactive effect of learning methods and emotional intelligence on students' ability to write narrative English texts at students. This is evidenced by the summary of Sig. 0.047<0.05, with Fcount=4.058.key words: learning Methods; emotional Intelligence; ability to write english narrative texts.